2022
DOI: 10.1101/2022.02.28.482316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcranial random noise stimulation of the primary visual cortex but not retina modulates visual contrast sensitivity

Abstract: Transcranial random noise stimulation (tRNS) has been shown to significantly improve visual perception. Previous studies demonstrated that tRNS delivered over cortical areas acutely enhances visual contrast detection of stimuli when tRNS intensity is optimized for the individual. However, it is currently unknown whether tRNS-induced signal enhancement could be achieved within different neural substrates along the retino-cortical pathway and whether the beneficial effect of optimal tRNS intensities can be repro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Similar to other studies investigating resonance-like effects (Potok et al, 2022a; van der Groen and Wenderoth, 2016), our results have revealed large variability among participants in terms of the optimal intensity resulting in the strongest modulation of visual contrast sensitivity ( Figure 5B , Figure 6B ). However, consistent with the effects of tRNS-induced online modulation of contrast processing in V1 shown previously (Potok et al, 2022a; van der Groen and Wenderoth, 2016), the effects of individualized hf-tACS intensity were replicated on the independent VCT data set collected within the same experimental session ( Figure 5C , Figure 6C ), suggesting consistent beneficial resonance-like influence of hf-tACS on signal enhancement.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to other studies investigating resonance-like effects (Potok et al, 2022a; van der Groen and Wenderoth, 2016), our results have revealed large variability among participants in terms of the optimal intensity resulting in the strongest modulation of visual contrast sensitivity ( Figure 5B , Figure 6B ). However, consistent with the effects of tRNS-induced online modulation of contrast processing in V1 shown previously (Potok et al, 2022a; van der Groen and Wenderoth, 2016), the effects of individualized hf-tACS intensity were replicated on the independent VCT data set collected within the same experimental session ( Figure 5C , Figure 6C ), suggesting consistent beneficial resonance-like influence of hf-tACS on signal enhancement.…”
Section: Discussionsupporting
confidence: 90%
“…In both experiments hf-tACS stimulation (hf-tACS triangle in experiment 1 or hf-tACS sine in experiment 2) was delivered with 0.75mA, 1mA, and 1.5mA amplitude (peak-to-baseline), resulting in maximum current density of 60 which is below the safety limits of 167 for transcranial electrical stimulation (Fertonani et al, 2015). These intensities were selected based on previous studies investigating effects of tRNS on contrast sensitivity (Potok et al, 2022a; van der Groen and Wenderoth, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations